Analisis pengaruh penambahan ion H+ pada sintesis material mesopori Al-MCM-41 menjadi H-MCM-41 - Soenandar Milian Tompunu Tengker; Iip Izul Falah (Jurnal Kimia Fullerene, 2018)
The synthesis of mesoporous Al-MCM-41 material made into H-MCM-41 has been done by mixing 5 grams of Al-MCM-41 synthesis into 100 ml of 0.5 M NH4Cl solution, then filtered and washed and dried in an oven at temperature 80 oC for 24 hours. The acid sites contained in the mesoporous material of H-MCM-41 are the Brønsted acid sites (B) and Lewis acid sites (L). The mesoporous material of H-MCM-41 synthesis shows morphological form of hexagonal pore such as honeycomb. It also makes clear that CTAB as a pore structure steering agent has succeeded in forming a hexagonal phase pore from mesoporous H-MCM-41 synthesized material. The size of the pore diameter of the mesoporous material of H-MCM-41 synthesis was 2.88 Å measured using a measuring ruler based on the scale of the resulting image analysis using TEM.